Knowledge of Dental Caries With Pop-Up Book Media for Children Aged 9-11 Years at Hos Education Surabaya Learning Guidance 2025 - Sari, Wahyu Indah Ratna; Hadi, Sunomo; Edi, Imam Sarwo (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Maintaining human health, especially dental and oral health, is crucial for life. Because dental and oral health are closely related to overall body health, they cannot be ignored. Maintaining dental and oral hygiene can be a long-term investment in life, while poor dental and oral health can disrupt daily activities and cause productivity problems. Tooth decay is the result of a number of problems, including Indonesians’ lack of awareness of dental and oral health. Using pop-up books as a medium, questionnaires were distributed before and after the educational intervention as part of a descriptive research design. The data processing and analysis methods employed in this study included calculating responses based on each respondent’s response and then calculating the average. The findings were then tabulated and converted into percentages. Based on the research results, knowledge about dental caries was assessed as low before the pop-up book intervention. Lack of knowledge about dental caries in children can result in low levels of understanding, which ultimately can lead to poor dental and oral health. After the pop-up book intervention, the results showed an improvement to the good category. The media design used in this intervention, which was tailored to the children’s needs, was a driving factor in this improvement. Learning media is a tool that can help simplify and increase learning efficiency while enhancing knowledge.